Exploração de Euterpe edulis Mart. (Arecaceae): efeitos sobre a estrutura de comunidades vegetais - Silva, Talita Ariela Sampaio e (Universidade Federal de São Carlos, 2015)
The harvesting of non-timber forest products (NTFPs) has been considered as a low-impact activity. However, the increasing demand of these products made greater the exploitation, which may cause depletion of resources in Nature. Euterpe edulis Mart. (Arecaceae) is one of the most studied plant species in Brazil, because it is economically important, listed among the most relevant products provided by Atlantic Rainforest. Moreover, this species is considered ecologically important, because it is a valuable food resource for fauna. In natural conditions, E. edulis is the most abundant species in Atlantic Rainforest. Nevertheless, illegal and massive harvesting lead the species to local extinction in some remnants, which resulted in the inclusion of the palm tree amongst the endangered plant species in Brazil. In this context, this study aimed to evaluate the impact of palm tree harvest on diversity at seed rain, regeneration layer and their relationship with the adult plant community. Thus, this study was carried out in two areas at Ilha do Cardoso State Park, both of them with the same land use history, despite the occurrence of massive palm heart harvest within one of them until 20 years ago. At these areas, we sampled seed rain with and without pulp, the regeneration layer and the adult plant community. The major motivations for this study were to apply diversity analysis on the assessment of harvesting impact, and to provide scientific information to the establishment of viable guidelines to the sustainable harvest of palm tree products. Our results showed that the abundance of E. edulis is related to the change of diversity patterns and species composition in seed rain and regeneration layer, and may have an influence on species composition in the future. This confirms the general hypothesis of this study, i.e. the disturbance caused by palm heart harvesting causes changes on species abundance enough to modify plant community structure. These changes could be detected even it has been 20 years after the end of illegal harvesting within the harvested area. The results also indicate that it is viable to make the sustainable harvest of E. edulis products, considering a selective removal of adult individuals and avoiding total suppression of clumps of palm tree. These actions promote heterogeneity on species composition of seed rain and regeneration layer.
Keywords: Ecologia vegetal; Ecologia de comunidades; Chuva de sementes; Regeneração (Biologia); Florestas; Diversidade biológica; Diversity indices; Species composition; Richness; Biodiversity; CIENCIAS BIOLOGICAS::ECOLOGIA